Analisis Unsur Intrinsik Dan Nilai-Nilai Yang Terkandung Dalam Cerpen Mirror, Mirror On The Wall Karya Dewi Lestari - Mirya Anggrahini Nimpuno (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
This article entitled : Analisis Unsur Intrinsik dan Nilai-Nilai yang Terkandung dalam Cerpen Mirror, Mirror on The Wall karya Dewi Lestari.” The writer wants to show the theme, the characters, setting, and plot of the Cerpen. The writer used a structural approach method in conducting this research. In the structural approach method, the writer completed the research by studying the internal aspects of the cerpen. Based on the analysis, it indicates that major-protagonist character in Mirror, Mirror on The Wall, Saya because the story is dominated by Saya. Mereka is called the major-antagonist character because they are the master mind of the conflict. The theme of the story is about life is made of choices. The setting of the story are place, time, social that connects to the main character.